The Work of Eugène Freyssinet: The Most Significant Bridges of his Career - Jartoux, Pierre (Docomomo Journal, 2011)
From 1904, when his career began, until 1962, when he died, Eugène Freyssinet did not stop building or advising on all aspects related with his work. To give an idea of his interest in the field of bridges, we selected the following: the Veurdre and Plougastel bridges as reinforced concrete examples and the Luzancy, the Marne and the Caracas La Guaira highway bridges as prestressed concrete works. In these brief descriptions, rather than the technical nature of the design, we have focused on intuition and innovation which made these works models and which inspired many engineers to continue working respecting quality.